Fluidex: The Fluid Engineering Abstracts Database - Sandy Lewis; Sharon Shafer; Bob Heyer-Gray (Issues in Science and Technology Librarianship)
This article reviews the Fluidex database published by Elsevier Science. It provides a source of information for all aspects of fluid engineering, fluids' behavior and applications.